The relationship beetween administration and users in Mali : contribution at the study of administrative law in african subsaharian states with a french institutional tradition - (:unkn) unknown (My University, 2011)
In the deep interest of the political democratization movements that the Sub-Saharan African States have established since the 1990's, the improvement of the relationships between the government and citizens has been quickly showed as one of the major targets of the procedures of reforming the State. However, as its achievement requires the adoption of a judicial framework for the welfare of citizens, the Malian example highlights, at the same time, the paradox which the political authorities are confronted to, and the challenge they have to take up on the reform aimed. By examining administrative law in the African territory, precisely its organizational and legitimizing functions, legal analysis performed using an interdisciplinary approach about relationships between government and citizens in Mali, suggests the "overhaul" of the production process. Between the principals of the judicial globalisation and legitimization of the state power; the administrative law would serve as an effective tool of the implementation of development public policies.
Keywords: African Research